PTFE-Doped CeO2 Films: Synthesis, Characterization and Properties - Taga, Y.; Nishimura , K.; Hisamatsu, Y. (Journal of Coating Science and Technology, 2020)
Multi-functional hybrid films were developed by doping PTFE into CeO2 by co-sputtering of CeO2 and PTFE targets. The hybrid films formed on borosilicate glass substrate containing from 5 to 15 vol. % PTFE in CeO2 showed UV shielding, high indentation hardness, hydrophobicity, optical transmittance in visible light, and high bending crack resistance. Optical properties of 100 nm thick CeO2 -5 vol. % PTFE film revealed UV light shielding of more than 80 % at 380 nm and visible light transmittance higher than 80 %. Indentation hardness measured under the load of 0.001mN was more than 16,000N/mm2 of 2.7 times higher than the glass substrate. No crack in the film was observed by bending 1.5 cm in diameter. Furthermore, the hydrophobic surface property was evaluated by the water contact angle to be higher than 90 degrees. Preliminary characterization of the CeO2-PTFE film using XPS and XMA revealed that chemical states of F in sputter doped PTFE in CeO2 can be considered to exist as C-F and Ce-F compounds. On the other hand, chemical states of Ce changed partially from Ce+4 (CeO2) to Ce+3 (Ce2O3 or CeF3) with increasing doped PTFEF in the film. In this rapid communication, we preliminary described the optical, mechanical and chemical properties of newly developed hybrid CeO2-PTFE films prepared by sputtering.